Effective Analgesia with Bilateral Erector Spinae Plane Catheters for a Patient with Traumatic Rib and Spine Fractures - L. Klesius; K. Schroeder (Case Reports in Anesthesiology)
Pain management in trauma patients with acute rib and spine fractures presents a challenge for the anesthesiologist and achieving adequate analgesia is important in preventing pulmonary complications. Unfortunately, neuraxial techniques are often challenging or contraindicated due to spine fractures or coagulopathy. Erector spinae plane (ESP) blocks provide an alternative regional anesthetic technique to manage pain. We describe a case of bilateral ESP catheters placed intraoperatively after spinal instrumentation in a patient with bilateral rib and spine fractures sustained in a tractor rollover crash. Prior to surgery, the patient had inadequate pain control and poor respiratory function despite multimodal analgesia. With the addition of bilateral ESP catheters, the patient’s pain control improved and he was weaned from respiratory support. ESP blocks have been shown to provide effective analgesia in patients with rib fractures; however, the utilization of these blocks has not been described in patients with spine fractures undergoing spinal instrumentation. Thus, ESP blocks provide a simple alternative to providing surgical and trauma analgesia when neuraxial techniques are contraindicated. The success of bilateral ESP catheters in our patient indicates a further area for application of ESP blocks in patients undergoing spine surgery with acute traumatic spine fractures.